A robust and eco-friendly waterborne anti-corrosion composite coating with multiple synergistic corrosion protections. (1st March 2022) - Lin, Dan; Wang, Xiao; Zhang, Meng; Yuan, Sicheng; Xu, Fei; Bao, Di; Wang, Huaiyuan
Abstract: Environmentally friendly waterborne coatings have received significant attention recently due to their lower volatile organic compounds (VOCs) emission than solvent-based coatings, but their practical applications are severely limited by poor barrier properties. Herein, a novel and robust waterborne OBN-PA-Zn-D/WEP anti-corrosion composite coating was successfully fabricated by utilizing hydroxyl-functionalized h-BN (OBN) nanosheets, phytic acid (PA), Zn 2+ and dicyandiamide. Due to the π-π interactions between OBN and organic-inorganic PA-Zn-D complex, the dispersibility of OBN-PA-Zn-D nanosheets was improved, which was beneficial for enhancing the physical barrier properties of OBN-PA-Zn-D/WEP composite coating. After adding dicyandiamide, the interface compatibility between OBN-PA-Zn-D nanosheets and the waterborne resin matrix was significantly improved, greatly reducing the defects inside the OBN-PA-Zn-D/WEP composite coating. In addition, PA and Zn 2+ formed protective layer in the defect area to inhibit the corrosion of anode and cathode. Therefore, under the effect of multiple synergistic corrosion protections, the eco-friendly waterborne OBN-PA-Zn-D/WEP composite coating exhibited unique anti-corrosion performance that was greatly improved compared with the conventional waterborne epoxy coatings. Highlights: A robust and eco-friendly waterborne anti-corrosion composite coating was prepared. OBN-PA-Zn-D/WEP composite coating provided strong corrosion protection. Physical barrier, corrosion inhibition and interface enhancement synergistically enhance anti-corrosion ability.